2021
DOI: 10.1093/intimm/dxab020
|View full text |Cite
|
Sign up to set email alerts
|

CD49d marks Th1 and Tfh-like antigen-specific CD4+ T cells during Plasmodium chabaudi infection

Abstract: Upon activation, specific CD4 + T cells upregulate the expression of CD11a and CD49d, surrogate markers of pathogen-specific CD4 + T cells. However, using TCR transgenic mice specific for a Plasmodium antigen, termed PbT-II, we found that activated CD4 + T cells develop not only to CD11a hiCD49d hi cells, but also to CD11a hiCD49d lo cells during acute Plasmodium infection. CD49d hi PbT-II cells, localized in the red pulp of spleens, expressed transcription factor T-bet, and produced IFN-γ, indicating that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 44 publications
1
9
0
Order By: Relevance
“…4B), as well as capturing higher frequencies of CXCR5 + cells compared to a previous approach of examining CD11a hi CD49d + cells (Extended Data Fig. 6A-B) [41]. Splenic CD11a hi CXCR3 + CD4 + polyclonal T cells and GFP + PbTII cells were recovered 7 days p.i.…”
Section: Resultsmentioning
confidence: 77%
“…4B), as well as capturing higher frequencies of CXCR5 + cells compared to a previous approach of examining CD11a hi CD49d + cells (Extended Data Fig. 6A-B) [41]. Splenic CD11a hi CXCR3 + CD4 + polyclonal T cells and GFP + PbTII cells were recovered 7 days p.i.…”
Section: Resultsmentioning
confidence: 77%
“…Using TCR transgenic PbTIIs, we had noted varying magnitudes and dynamics of transcriptional responses mounted by splenic antigen-experienced CD4 + T cells during re-infection. To determine the relevance of our findings to TCR diverse polyclonal CD4 + T cells, we first transferred naïve PbTIIs, infected and drug-cured mice as above, and determined if co-expression of the markers CD11a, as previously reported 25,26,27 , and CXCR3 (as suggested from our previous study 14,28 ) would permit flow-cytometric enrichment of polyclonal, activated CD4 + T cells (Figure 6A). We noted firstly, that PbTIIs prior to and 2 days after re-infection expressed high levels of CD11a and CXCR3 (Figure 6A).…”
Section: Tcr Diverse Antigen-experienced Cd4 + T Cells In the Spleen ...mentioning
confidence: 77%
“…It is possible that the CD8 T cell response induced following vaccination may not be entirely mCAR12 and mCDK12 specific. A recent study using a Plasmodium infection model indicated that activated CD4 T cells develop into both CD11a hi CD49d hi type 1 helper T (Th1) cells and CD11a hi CD49d lo follicular helper T (Tfh)-like cells ( 37 ). The exact mechanism through which neoantigen-specific CD4 T cells mediate tumor regression is unknown at this point.…”
Section: Discussionmentioning
confidence: 99%
“…hi CD49d hi type 1 helper T (Th1) cells and CD11a hi CD49d lo follicular helper T (Tfh)-like cells(37). The exact mechanism through which neoantigen-specific CD4 T cells mediate tumor regression is unknown at this point.…”
mentioning
confidence: 99%